Acquisition of EMT phenotype in the gefitinib-resistant cells of a head and neck squamous cell carcinoma cell line through Akt/GSK-3β/snail signalling pathway - Maseki, S (Nature Publishing Group, 2012)
BACKGROUND: Epithelial mesenchymal transition (EMT) is known to be associated with chemoresistance as well as increased invasion/metastasis. However, the relationship between EMT and resistance to an epidermal growth factor receptor (EGFR) -targeting drug in head and neck squamous cell carcinoma (HNSCC) remains unknown. In this study, we investigated the acquisition of EMT by gefitinib in HNSCC cell line (UMSCC81B). METHODS: We isolated fibroblastoid variant (81B-Fb) from gefitinib-resistant UMSCC81B-GR3 cells obtained after increasing the doses of gefitinib treatment in vitro and examined EMT and its underlying mechanism. RESULT: 81B-Fb cells exhibited fibroblast-like morphology, increased motility, loss of E-cadherin, acquisition of vimentin and snail expression. In 81B-Fb cells, downregulation of EGFR, which is mediated by increased ubiquitination, and activation of downstream protein kinase B (Akt), glycogen synthase kinase-beta (GSK-3β) signalling and upregulation of snail expression were observed compared with UMSCC81B cells. LY294002, but not U0126, suppressed foetal bovine serum or heregulin-β1-induced phosphorylation of Akt/GSK-3β and snail expression together with the inhibition of 81B-Fb cell motility. Furthermore, forced expression of EGFR resulted in partial restoration of gefitinib sensitivity and reversal of EMT. CONCLUSION: These results suggest that EMT in the gefitinib-resistant cells is mediated by the downregulation of EGFR and compensatory activation of Akt/GSK-3β/snail pathway.